2020
DOI: 10.1136/bmjdrc-2019-000942
|View full text |Cite
|
Sign up to set email alerts
|

Glucose homeostasis is impaired in mice deficient in the neuropeptide 26RFa (QRFP)

Abstract: Significance of this studyWhat is already known about this subject? ► 26RFa is a biologically active peptide produced in abundance in the gut and the pancreas. ► 26RFa has been found to regulate glucose homeostasis by acting as an incretin and by increasing insulin sensitivity.What are the new findings?► Disruption of the 26RFa gene induces substantial alteration in the regulation of glucose homeostasis, with in particular a deficit in insulin production by the pancreatic islets, assessing therefore the notion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Primeaux ( Takayasu et al, 2006 ) has shown that, after 3 weeks on a high-fat (55%) diet, consumption increased the concentration of preproQRFP mRNA in the VHM/ARC, but not in the LHA. In contrast, Beck et al ( El-Mehdi et al, 2020 ) have shown that the expression of 26RFa/QRFP was undetectable in Long-Evans rats fed on a high-fat diet, yet in the control group (30% fat) the expression was lower than in the low-fat (5%) diet group. Nevertheless, the application of a caloric restriction diet for 10 weeks in B6 mice resulted in no changes in the expression of 26RFa and GPR103 ( Méquinion et al, 2017 ).…”
Section: Neuropeptide 26rfamentioning
confidence: 89%
See 1 more Smart Citation
“…Primeaux ( Takayasu et al, 2006 ) has shown that, after 3 weeks on a high-fat (55%) diet, consumption increased the concentration of preproQRFP mRNA in the VHM/ARC, but not in the LHA. In contrast, Beck et al ( El-Mehdi et al, 2020 ) have shown that the expression of 26RFa/QRFP was undetectable in Long-Evans rats fed on a high-fat diet, yet in the control group (30% fat) the expression was lower than in the low-fat (5%) diet group. Nevertheless, the application of a caloric restriction diet for 10 weeks in B6 mice resulted in no changes in the expression of 26RFa and GPR103 ( Méquinion et al, 2017 ).…”
Section: Neuropeptide 26rfamentioning
confidence: 89%
“…Recently, the QRFP system is a popular target for research on metabolic homeostasis, glucose and lipid metabolism, pancreas function, and obesity ( Mulumba et al, 2010 , 2015 ; Méquinion et al, 2017 ; Prévost et al, 2019a , b ; El-Mehdi et al, 2020 ).…”
Section: Neuropeptide 26rfamentioning
confidence: 99%
“…The QRFPR gene (also known as GPR103 gene) encodes a G-protein-coupled receptor that is expressed in brain, urinary bladder, thyroid gland, human pancreatic β-cells, and so on. 21 Recent data indicate that QRFPR and its ligand QRFP are key regulators of glucose homeostasis 22 by increasing insulin sensitivity and insulin secretion, 23 , 24 as well as preventing pancreatic β-cells death and apoptosis. 25 Besides, a locus on chromosome 4q27 that is approximately 625kb downstream the QRFPR gene was reported to be associated with a number of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…N-methylation of Phe 22 (LV-2066, 25) and Phe 26 (LV-2242, 27) nullified the activity of the parent compound (EC 50 > 10 µM, Table 2) revealing the critical role of the corresponding NHs in forming an H-bond with the hQRFPR pocket residues or another residue of the peptide, whereas N-methylation of Phe 24 (LV-2233, 26) did not impair the whole activity of LV-2021 (1). The corresponding Tic-containing analogs (28)(29)(30) did not totally confirm these data since [Tic 24 ]26RFa (20)(21)(22)(23)(24)(25)(26) (20)(21)(22)(23)(24)(25)(26) (LV-2211, 28) was 5-fold more potent than 26RFa (20)(21)(22)(23)(24)(25)(26) (LV-2021, 1) (Figure 3D). It is thus also plausible that the structural constraint induced by the Tic 22 residue may keep the side chain in a favorable conformation for receptor activation, which was less accessible by free rotation in the native Phe side chain.…”
Section: Impact Of Modifications Of Each Phenylalanine Residuementioning
confidence: 98%
“…There is also evidence that 26RFa and/or QRFP regulate several other neuroendocrine and cognitive functions including reproduction [ 17 , 18 ], anxiety [ 19 ], memory [ 20 ], cardiovascular activity [ 8 ] and nociceptive transmission [ 21 , 22 , 23 ], some of which depend, at least in part, on off-target interaction with QRFPR-related receptors [ 24 , 25 ]. In addition, recent data reveal that the 26RFa/QRFPR system controls glucose homeostasis at the periphery by increasing insulin sensitivity and inhibiting hepatic glucose production [ 26 , 27 , 28 , 29 ]. Thus, QRFPR positions as an attractive target for the development of innovative drugs.…”
Section: Introductionmentioning
confidence: 99%